2010
DOI: 10.1002/hed.21352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharyngocutaneous fistula between patients followed by primary laryngopharyngectomy and salvage laryngopharyngectomy for advanced hypopharyngeal cancer

Abstract: Preoperative radiation therapy and hypo-albuminemia increase the fistula rate significantly. A prolonged hospital course was noted among all fistula patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 14 publications
7
75
3
2
Order By: Relevance
“…In our study, we demonstrated an increased incidence of PCF in patients with preoperative RT, which is in agreement with the majority of literature reports (13)(14)(15)(16)(17)(18)(19)(20). While, some studies did not find any association between preoperative RT and PCF formation (5-7, 21, 22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we demonstrated an increased incidence of PCF in patients with preoperative RT, which is in agreement with the majority of literature reports (13)(14)(15)(16)(17)(18)(19)(20). While, some studies did not find any association between preoperative RT and PCF formation (5-7, 21, 22).…”
Section: Discussionsupporting
confidence: 92%
“…Although this opinion has many justifications, the early primary surgical closure of an existing PCF is not always easy and successful. According to our experience, as some PCFs spontaneously close with appropriate treatment, our initial approach was conservative treatment, as reported in other studies (7,13,14). However, if 2 weeks of conservative treatment fails, surgical intervention is required to attempt to close the fistula.…”
Section: Discussionmentioning
confidence: 68%
“…Pharyngocutaneous fistula development is a common complication of total laryngectomy resulting in increased length of hospital stay [8,1012], delayed oral intake [12,29], delay of adjuvant therapy [26] and often the need for complex wound care and additional procedures for fistula closure [11,12]. Given the frequency of PCF and its significant morbidity, it is important to identify salient risk factors and potential measures for improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent postoperative complication is the development of a pharyngocutaneous fistula (PCF), which occurs with variable frequencies of 3% to 65% in reported series, most falling within 10%–40% [7]. PCF is an early complication [8,9] that causes increased length of hospital stay and delayed initiation of oral diet, and requires complex wound care, occasionally necessitating additional surgery for closure [8,1012]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation